Book review: Clammer, John. 2012: Cultural, Development and Social Theory: Towards an Integrated Social Development. (October 2014) - Fontefrancesco, Michele
Clammer, John. 2012: Cultural, Development and Social Theory: Towards an Integrated Social Development . London: Zed Books. viii + 291 pp. £18.99 paperback. ISBN: 9781780323145.